MANAJEMEN PEMBINAAN SPIRITUAL DI SMA SWASTA NURANI UNTUK MENGATASI KRISIS MORAL SISWA DI ERA SOCIETY 5.0 - Fadhilah, Farras; Siahaan, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Technological developments in the Society 5.0 era have had complex effects on students’ morality, one of which is the emergence of a moral crisis in the school environment. This study aims to describe the management of spiritual guidance at Nurani Private High School as an effort to address the moral crisis among students in this era. The method used is qualitative, with data collection through interviews, observations, and documentation involving the principal, teachers, and students. The results of the study indicate that spiritual guidance at this school is implemented systematically through the stages of planning, implementation, and evaluation, focusing on strengthening students’ religious values and character. Although there are challenges in the form of the negative influence of digital technology, spiritual guidance has proven effective in fostering discipline, responsibility, and ethical communication among students. However, improvements are needed in program evaluation and parental involvement to optimize these efforts. This study underscores the importance of adaptive and sustainable spiritual guidance management in shaping students’ character so they can behave morally in the digital age